Pengaruh Model Pembelajaran Quantum Teaching terhadap Hasil Belajar Siswa pada Tema 1 Indahnya Kebersamaan Sub Tema 2 Kebersamaan dalam Keberagaman Kelas IV SD Negeri 091421 EMPL Bah Butong - Siti Nur Cahyani; Muktar B. Panjaitan; Hetdy Sijabat (Departement of Mathematics Education, 2023)
This study aims to find out: the effect of the quantum teaching learning model on student learning outcomes in theme 1 the beauty of togetherness, sub-theme 2 of togetherness in diversity in class IV elementary school 091421 empl bah butong t.a 2022/2023. This research is a quantitative research using the test method. The population of this research is 33 students. While the samples in this study were 33 students. The instrument used is in the form of a multiple choice test that has been tested for validity and reliability. The results of the study at the 0.05 level show that: there is an influence of the quantum teaching learning model on student learning outcomes in theme 1 sub-theme 2 togetherness in diversity in class IV sdn 091421 empl bah butong based on test analysis shows that the value of sig (2-tailed) is 0, 00 <0.05, where ho is rejected and ha is accepted so it can be concluded that there is a significant effect between improving student learning outcomes.